A Bi-Directional, Liquid-Spring-Magnetorheological-Fluid-Damper System - Maus, Nicholas; Gordaninejad, Faramarz (Frontiers in Materials, 2019)
The goal of this study was to demonstrate the feasibility of a novel fail-safe, bi-directional liquid spring, controllable magnetorheological fluid damper (BDLS-CMRD). This research introduces a device with independently pre-set spring forces in compression and rebound combined with controllable MR fluid damping. The BDLS-CMRD can potentially replace traditional metal spring-damper suspension systems. Bulky and heavy metal spring-damper suspension systems can be upgraded to the smaller and lighter BDLS-CMRD, reducing the mass of vehicle suspensions. In this work, a BDLS-CMRD was designed, fabricated, tested and evaluated in three phases. The first design phase demonstrates the concept of a liquid spring with different spring forces in compression and rebound. The second phase incorporates viscous fluid damping of pure silicone fluid with the first phase BDLS. The final design phase combines a controllable magnetorheological fluid (MRF) damper with the first phase BDLS. This study presents the response of the BDLS-CMRD in a wide range of preloaded conditions and frequencies. Experiments were performed for sinusoidal displacements in the quasistatic and dynamic ranges to evaluate the performance of the BDLS-CMRD under different magnetic fields. The experimental results demonstrate that the device operates with significantly different spring forces from the compression to rebound regions, while providing passive viscous fluid damping or controllable MR fluid damping. This system has successfully demonstrated that the utility of a bi-directional liquid spring can be combined with the reliability of passive viscous fluid damping and the capabilities of controllable MR fluid damping into one compact and versatile device.